(3QSGdI aj HbGA GdfaS GdEfSGfjI HYO GdeaGQbIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3bGd YdGeI GdYGde CaGO cd GdeMbbhf ai HbGA GdfaS GdEfSGfjI HYO s
(3BNQgG (B:s
(3ai cdGe GdYdeGA ai gPG GdHGH (B, (3hGddg CYde HMbjbI GdMGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd eNJdaIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs